J.AYMURZAEV – QARAQALPAQ SATIRALÍQ PROZASÍNÍŃ BASLAWSHÍLARÍNÍŃ BIRI SÍPATÍNDA - Jaqsılıqova, A.S. (ILIM hám JÁMIYET, 2021)
The article is devoted to one of the least studied topical issues of Karakalpak literature. It is described the process of studying satire in the karakalpak literature of XXth century, its features, the development stages of satire prose. More over, there interpreted satirical images in the work of the great karakalpak writer J.Aymurzaev Amudarya boyinda (At the bank of Amudarya).